The Impact of Diagnostic Status on Quality of Life in Irritable Bowel Syndrome - Cassar, Gillian Eleanor; Youssef J, George; Knowles, Simon R; Moulding, Richard; Austin, David (Turkish Journal of Gastroenterology, 2021)
Background: The aim of the study was to examine the impact of diagnostic status (i.e., having a clinical diagnosis of irritable bowel syndrome (IBS) or being symptomatic but undiagnosed on quality of life (QoL)). We also examined whether the relationships between QoL and variables such as symptom frequency, pain catastrophizing, visceral sensitivity, and psychological distress are moderated by diagnostic status. Methods: The online sample comprised 404 participants (Mage = 33.59, SD = 12.43), of which 98 had been diagnosed with IBS and 306 were symptomatic but undiagnosed. Results: The findings suggest that even after adjusting for symptom frequency, those diagnosed with IBS experience poorer QoL, relative to those without a diagnosis. Moreover, there was evidence that the relationship between specific QoL domains (namely, sex, food avoidance, and health worry) and psychological variables (namely, pain catastrophizing, and depression) was moderated by diagnostic status. Conclusion: The results indicate that diagnostic status in relation to IBS has psychological implications for QoL outcomes distinct from symptom frequency, age, and gender. This highlights a substantial gap in our current understanding of how a diagnosis of IBS can impact the lives of those suffering from IBS symptomology and calls into question the intended purpose of diagnosis.